2016
DOI: 10.1039/c6cc02807a
|View full text |Cite
|
Sign up to set email alerts
|

Reversible transformation between ionic liquids and coordination polymers by application of light and heat

Abstract: Reversible transformation between an ionic liquid and a coordination polymer by application of light and heat has been achieved. Ultraviolet light irradiation transforms the transparent liquid to a yellow solid; a reverse reaction occurs due to the application of heat. The transformation accompanies drastic switching of intra- and intermolecular coordination bonds of a ruthenium complex. This is a novel material conversion methodology that connects the fields of ionic liquids and coordination polymers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 20 publications
3
42
0
Order By: Relevance
“…These polymers have attracted much attention in recent years owing to their functionality, such as magnetism and gas absorption properties. Previously, we reported on ionic liquids that undergo reversible transformation to coordination polymers by application of light and heat . However, the resultant coordination polymers did not exhibit gas absorption properties because they were non‐porous.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…These polymers have attracted much attention in recent years owing to their functionality, such as magnetism and gas absorption properties. Previously, we reported on ionic liquids that undergo reversible transformation to coordination polymers by application of light and heat . However, the resultant coordination polymers did not exhibit gas absorption properties because they were non‐porous.…”
Section: Figurementioning
confidence: 99%
“…The design of these ionic liquids is based on the photochemical reactivity of ruthenium sandwich complexes shown in Figure ; UV light irradiation of [Ru(C 5 H 5 )(arene)] + in acetonitrile solution leads to the elimination of the arene ligand to produce an acetonitrile‐coordinated cation [Ru(C 5 H 5 )(CH 3 CN) 3 ] + . The above‐mentioned reversible transformation between ionic liquids and coordination polymers is also based on this mechanism . In the current study, we used [B(CN) 4 ] − as the counter anion, so that coordination of the polycyano anion, instead of acetonitrile, to the Ru ion occurs upon UV irradiation of the ionic liquid.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, stimuli‐responsive ILs have attracted much attention in this decade . We have previously demonstrated that functional ILs exhibit electronic property changes and structural transformation by application of magnetic fields, exposure to vapors and gases, and application of light and heat . Several photo‐responsive ILs containing photochromic molecules such as azobenzenes, stilbenes, cinnamates, and diarylethenes have also been reported.…”
Section: Figurementioning
confidence: 99%
“…[2] We have previously demonstrated that functional ILs exhibit electronic property changes and structural transformation by application of magnetic fields, [3] exposure to vapors and gases, [4] and application of light and heat. [5] Several photoresponsive ILs containing photochromic molecules such as azobenzenes, [6] stilbenes, [7] cinnamates, [8] and diarylethenes [9] have also been reported. These photochromic ILs are useful for various application because they exhibit reversible color and physical property changes owing to a structural isomerization between two isomers.…”
Section: Photochromic Ionic Liquids Containing Cationic Spiropyran Dementioning
confidence: 99%